Implementation Of The Tanggap Leungitkeun Stunting (Taleus) Policy - Danil, Mahmud; Husein Maruapey , Muhammad; Rusliandy , Rusliandy (Jurnal Sosial Humaniora, 2025)
This study originates from the serious challenges related to stunting in Indonesia, particularly in Bogor City, which has a significant prevalence and requires innovative handling. Stunting affects children's health, cognitive abilities, and long-term productivity, which can influence economic growth. One of the targets of the Sustainable Development Goals (SDGs) is to reduce the stunting rate by 40% by 2025. The Bogor City Government has designed the Tanggap Leungitkeun Stunting (TALEUS) innovation program to reduce stunting rates through integrated interventions. This study aims to analyze the implementation of the TALEUS policy, evaluate the program's effectiveness in reducing stunting rates, and identify factors contributing to its success and challenges in its implementation. This study employs a qualitative approach with a descriptive method, based on the policy implementation theory by Van Meter and Van Horn. Data were collected through in-depth interviews, field observations, and document analysis. The study subjects included healthcare workers, representatives from local government agencies (OPDs), posyandu cadres, and the targeted community groups of the program. The study results indicate that the implementation of TALEUS has been relatively successful, supported by social, economic, and political factors. The program adopts a life-cycle approach, including nutrition education, supplementary feeding (PMT), and child growth monitoring. Community participation and cross-sectoral support are considered strong, but further improvements in education and sustained collaboration are still needed. Before TALEUS was implemented, the stunting prevalence in Bogor City fluctuated, rising from 4.52% in 2019 to 10.66% in 2020, then decreasing to 3.25% in 2022. After the implementation of TALEUS, the stunting rate in February 2023 was recorded at 2.81%, demonstrating the program’s effectiveness in accelerating stunting reduction. In conclusion, TALEUS has great potential to reduce stunting rates effectively through cross-sector collaboration and sustainable interventions. However, the long-term success of this program depends on consistent education and joint efforts from all stakeholders to achieve the Zero New Stunting target by 2024. Keywords: Policy Implementation, Stunting, TALEUS